Deoxygenation of Bio-oil from Calcium-Rich Paper-Mill Waste - Bashir, Muhammad Asif; Jahangiri, Hessam; Hornung, Andreas; Ouadi, Miloud (Chemical Engineering & Technology, 2020)
De-inking sludge, an ash-rich recycling paper solid waste, is generated in huge amounts. The catalytic deoxygenation potential of calcium-based de-inking sludge in co-pyrolysis mode with wood and its neat thermal conversion to sustainable biofuels are investigated. Wood, de-inking sludge, and their blends are processed in a thermocatalytic reforming (TCR) system. In the presence of de-inking sludge, the oxygen content in the organic phase decreases and the bio-oil calorific value improves as compared to the neat wood-derived bio-oil. The TCR processing of neat de-inking sludge produces a bio-oil with low oxygen content and higher calorific value.
CRIS-Team WoS Importer:2020-12-25